The Effectivity of Bioactive Compounds from Montanoa hibiscifolia Benth Plants in inhibiting the Growth of Candida albicans. - Askar Fardiansyah; Khotibul Umam; Wawan Sujarwo; Putu Agus Hendra Wibawa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Leucorrhoea is one of common disease in Indonesia that caused by infections of fungus Candida albicans. In dealing with this fungi, the synthetic and even an natural compound had used. Based on pre-screening data of the plants from botanical garden of Eka Karya Lipi Bali, there found apotential plant. This study aims to find the latest alternative treatment using the extract of Montanoa hiscifolia Benth plant from the collection of the